Chiral phase transition in a covariant nonlocal NJL model - General, I. (2001)
The properties of the chiral phase transition at finite temperature and chemical potential are investigated within a nonlocal covariant extension of the Nambu-Jona-Lasinio model based on a separable quark-quark interaction. We consider both the situation in which the Minkowski quark propagator has poles at real energies and the case where only complex poles appear. In the literature, the latter has been proposed as a realization of confinement. In both cases, the behaviour of the physical quantities as functions of T and μis found to be quite similar. In particular, for low values of T the chiral transition is always of first order and, for finite quark masses, at certain "end point" the transition turns into a smooth crossover. In the chiral limit, this "end point" becomes a "tricritical" point. Our predictions for the position of these points are similar, although somewhat smaller, than previous estimates. Finally, the relation between the deconfining transition and chiral restoration is also discussed.